1986
DOI: 10.1002/jcu.1870140812
|View full text |Cite
|
Sign up to set email alerts
|

Hemobilia: A cause of false‐negative ductal dilatation

Abstract: Ultrasound is a well-established method of evaluating bile duct size, with accuracy rates ranging from 86 to 93%' Reasons for false-negative interpretation in cases of obstructive jaundice include lack of ductal dilatation in the presence of a common duct stone, sclerosing cholangitis, tumor encasement of the ducts (either from metastatic or cholangiocarcinoma), ducts filled with "debris," and technical difficulties often related to prior surgery in the area.'-4 This case report illustrates another cause of fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Later, after contraction, the clot conforms to the tubular structure of the duct and may be mistaken for the true lumen. These potential problems limit the diagnostic utility of ultrasound [59,60]. Less specific findings are usually seen on ultrasound in patients with hemobilia including cholelithiasis, a dilated biliary tree, evidence of liver contusion, hepatic tumor, or pseudoaneurysm identified as anechoic mass with flow on color Doppler.…”
Section: Ultrasoundmentioning
confidence: 96%
“…Later, after contraction, the clot conforms to the tubular structure of the duct and may be mistaken for the true lumen. These potential problems limit the diagnostic utility of ultrasound [59,60]. Less specific findings are usually seen on ultrasound in patients with hemobilia including cholelithiasis, a dilated biliary tree, evidence of liver contusion, hepatic tumor, or pseudoaneurysm identified as anechoic mass with flow on color Doppler.…”
Section: Ultrasoundmentioning
confidence: 96%
“…Side view duodenoscope is useful in making the diagnosis of hemobilia. The yield of endoscopy is dependent on rate and duration of bleeding, all hemobilia patients had lower positive endoscopic findings 12.0-37.5% 8,34 but in clinical significant hemobilia suggested that the yield was close to 100.0% 32 and further investigation should be undertaken ( Figure 2).…”
Section: Investigationmentioning
confidence: 99%
“…These finding is limitation to diagnosis hemobilia. 34,35 Ultrasound is useful in diagnosis of underlying disease; cholelithiasis, biliary ascariasis, liver mass and pseudoaneurysm of hepatic artery (Doppler ultrasound).…”
Section: Ultrasoundmentioning
confidence: 99%